Comparative life history of coconut scale insect, aspidiotus rigidus reyne (hemiptera diaspididae), on coconut and magosteen - Cortaga, Cris Q.; Sison, Maria Luz J. (2019)
The devastation of millions of coconut palms caused by outbreak infestation of the invasive Coconut Scale Insect (CSI) Aspidiotus rigidus Reyne, has posed a serious threat to the industry in the Philippines.